Bishop's formula for a matrix polyhedron with a non-piecewise smooth boundary - Makhkamov, Erkin M. (Вестник Томского государственного университета. Математика и механика)
In this work, a matrix polyhedral domain is defined using a matrix ball. In this matrix polyhedral domain, an analogue of Bishop's formula for meromorphic functions of a special form is obtained.